Preparation and properties of porous L‐tryptophan imprinted latex membrane from core‐shell emulsion. Issue 3 (10th May 2012) - Lin, Meina; Li, Xiao; Zhang, Weiying; Ying, Xiaoguang
Abstract: Molecularly imprinted latex membrane (MILM) is prepared by core‐shell emulsion technique in the presence of a template molecule (L ‐Tryptophan). A hard inward and soft outward microstructure latex particle is designed to obtain MILM with both flexibility and impact strength. Molecularly imprinted layer with high crosslinking degree is grafted on the surface of core‐shell latex particles. NaCl, glucose, urea, polyethylene glycol, M w 300, etc., are added during the film‐forming process to produce porous microstructure in MILM. Fourier transform infrared spectroscopy (FTIR) and Scatchard analysis are used to investigate the interaction betweenL ‐Tryptophan and MILM and the binding ability of the resultant MILM, respectively. The functional binding and separation performances in aqueous medium towards template are carried out. The results reveal that the content and type of porogen and the shell composition have significant effects on adsorption capacity and separation ability. MILM with glucose as porogen shows high recognition towards the template with adsorption separation factor reaching 9.06. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :